The Role Of PD-1/PD-L1 Axis In Treg Development And Function: Implications For Cancer Immunotherapy - Cai, Jiajing; Wang, Dongsheng; Zhang, Guoyuan; Guo, Xiaolan (OncoTargets and therapy, 2019)
During the past decade, immunotherapy targeting immune checkpoints has become an important component of the treatment paradigm for numerous malignancies, especially PD-1/PD-L1 blockade which was demonstrated to rejuvenate disabled T cells in cancer patients to achieve long-term remissions. However, the clinical outcome of PD-1/PD-L1 targeted monotherapy against solid malignancies is not satisfactory which may be related with the intricate tumor microenvironment. As a vital suppressive immunocyte in tumor microenvironment, Tregs are characterized by PD-1 and PD-L1 and demonstrated to contribute to the tumor progression. The latest studies have suggested that Tregs might be involved in the treatment of PD-1/PD-L1 blockade and PD-1/PD-L1 axis could influence Treg differentiation and function. However, the complicated relationship between PD-1/PD-L1 pathway and Tregs has not been fully clarified. Here, we explored the role of PD-1/PD-L1 axis in Treg development and function, as well as the potential mechanisms of PD-1/PD-L1 blockade resistance related with Tregs. Meanwhile, we discussed the combination therapy aimed at targeting PD-1/PD-L1 axis and Tregs, hoping to provide novel insights for the future cancer treatment.